STRATEGI GURU DALAM MENINGKATKAN MOTIVASI BELAJAR PESERTA DIDIK PADA MATA PELAJARAN PPKn DI UPT SMAN 2 SELAYAR - Haris, Hasnawi; Kasmawati, Andi; Nur, Andi Armianti (Jurusan Pendidikan Pancasila dan Kewarganegaraan (PPKn), 2024)
This research aims to determine 1) Teacher efforts to increase students learning motivation in Civics subjects at UPT SMAN 2 Selayar. 2) Factors inhibiting teachers in increasing students' learning motivation in civics subjects at UPT SMAN Selayar.This research is a qualitative descriptive study. The types and sources of data used in this research are primary data sources and secondary data sources. Data collection techniques include: interviews and documentation. Data obtained from research results were processed using qualitative descriptive data analysis.The results of this research show that: (1) Teachers efforts to increase students’ learning motivation in civics subjects by explaining learning objectives to students, using varied learning methods, providing objective values to students, using ice breaking in learning, giving quizzes to student and giving praise to students successes. (2) The inhibiting factors for teachers in increassing students learning motivation in civics subjects are students laziness, students poor attitudes towards learning and differences in students levelss of intelegence.